DIET NUTRITION MANAGEMENT FOR TREATMENT OF ANGULAR CHEILITIS DESEASES IN CHILDREN - I Gusti Ayu Ari Agung; Dewa Made Wedagama; G.A.A. Hartini (International Journal of Applied Science and Sustainable Development (IJASSD), 2019)
Angular cheilitis or perleche is an inflammation reaction on the corner of the mouth, the condition is characterized by cracks and inflammation on both corners of the mouth. This paper aims to review about diet nutrition management for treatment of angular cheilitis disease. This study used review of descriptive. This study was a review of articles published on an online journal from 2013-2018, with the title of the article related to the research. Etiological factor of angular cheilitis may also vary, which in most cases is caused by nutritional deficiencies. Treatment of angular cheilitisis eliminating the etiology factors, and successful treatment of angular cheilitis depends on the cause topical therapy is likely to fail in nutritional deficiency. Management and treatment of angular cheilitisis with balanced nutrition and diet, especially protein, carbohydrate, vitamin A, B2, B3, B6, B12,C, E, biotin, folic acid and mineral Fe, Zn. Most of the angular cheilitis that occur can heal itself without antimicrobials, body’s defense system should be maintained or increased by administering vitamin supplements or multivitamins.